Purification, Characterization and Antifungal Activity of the Aspergillus niveus Chitinase Produced Using Shrimp Shells - Ornela, Pedro Henrique [UNESP]; Guimarães, Luis Henrique Souza (MDPI, 2024)
Chitinases are biotechnologically relevant enzymes that can be applied in such different sectors as pharmaceutical, food, environmental management, the biocontrol of pests and in the paper and cellulose industry. Microorganisms as filamentous fungi are the most important source of these biomolecules. The fungus Aspergillus niveus produces extracellular chitinase when cultured under submerged fermentation using shrimp shells, a residue generated by the fish industry, as a carbon source, for 96 h at 30 °C and 100 rpm. The particle size and concentration of the shrimp shells affected enzyme production. The chitinase was purified until electrophoretic homogeneity through the use of a Sephadex G-100 chromatographic column. It is a monomeric glycoprotein with a molecular mass of 47 kDa estimated using SDS-PAGE and 49.3 kDa determined using gel filtration. The carbohydrate content was 22.8%. The best temperature and pH for enzyme activity were 65 °C and 6.0, respectively. Approximately 80% of the enzymatic activity was preserved at pH 4.0 and 5.0 for 48 h, and the half-life (t50) was maintained for 48 h at 40 °C. Salts, EDTA and β-mercaptoethanol did not affect chitinase activity significantly, but organic solvents reduced it. The kinetic parameters determined using p-NPGlycNac were Km of 2.67 mmol L−1, Vmax of 12.58 U mg of protein−1, Kcat of 2.47 s−1 and K cat/Km of 0.93 s−1 mmol L−1. The A. niveus chitinase inhibited the growth of all fungal strains used, especially Trichoderma harzianum (MIC = 22.4 μg mL−1) and Penicillium purpurogenum (MIC = 11.2 μg mL−1). The chitinase produced by A. niveus presented interesting characteristics that indicate its potential of application in different areas.
Keywords: antifungal activity; Aspergillus; chitin; fungal fermentation